Her shape' intervention programme for obese women with high breast adiposity - Juliana N.; Shahar S.; Sahar M.A.; Ghazali A.R.; Manaf Z.A.; Noah R.M. (HEC Press, 2024)
Background and Objectives: Nutrition and physical activity interventions is beneficial in reversing obesity. However far too little attention has been paid to the effect of these interventions on breast tissues. Thus, the aim of this study was to explore the effect of a home-based dietary and physical activity intervention (the Her Shape Program) on metabolic parameters, blood biomarkers and adiposity at the breast. Methods and Study Design: A randomized controlled study was conducted on obese women with high breast adiposity ( < 0.1 Sm-1), aged 40-60 years in Klang Valley, Malaysia. Subjects were assigned to intervention (n = 16) and control group (n = 15). Intervention group received a home based health education package with close monitoring weekly, personal diet consultation and physical training in group. Assessment was ascertained at three time points; baseline, weeks 8 and 16. Outcome measures were the energy intake, physical activity, body composition, blood tests, blood biomarkers and electrical impedance tomography (EIT) quantitative values. Analyses were done using 2-way repeated measures ANOVA. Results and Conclusions: All subjects completed the program without any drop-out. The HSI group had 100% compliance towards the intervention program; their energy intake was reduced for approximately 35% and their activity score was increased for approximately 11%. A significant interaction effect was found in body weight, body mass index (BMI), total cholesterol/HDL, vitamin C intake and matrix metallopeptidase 9 (MMP-9) (p < 0.05). Interestingly, their EIT extremum values were also significantly increased indicating a reduction of breast adiposity. The intervention program was successful in improving body composition, physical activities, MMP9 and breast adipose tissue composition.